Enjeux communicationnels des recherches partenariales dans le contexte des open labs - Valérie Lépine; Fabienne Martin-Juchat (Communiquer)
Since the 1980s, in the continuity of the “new spirit of capitalism”, a dynamic has evolved under the generic term “open lab”. Conceived as places of creative and collective making, they would promote new productions of knowledge. A review of the research carried out over the last fifteen years with non-academic actors allows us to observe how these dynamics contribute to the acceptability and legitimacy of these new ways of doing research. A model of the communicational conditions of cooperation is proposed on the basis of six cases. These conditions question the teacher-researcher’s identity in partnership research, such as: the quality of inter-comprehension, the level of construction of a shared language, the emergence of a community of exchanges and practices––foundation of cooperation, the degree of reflexivity, and the emotional and relational skills mobilized. These conditions are necessary but not sufficient for the co-production of knowledge and methods.